1986
DOI: 10.1159/000226347
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors and Cancer Mortality in Italy: Correlational Excercise

Abstract: Mortality rates for 21 cancer sites in 20 Italian regions have been correlated with several economic and dietary variables (including alcohol and coffee consumption), patterns of cigarette smoking and reproductive habits. In both sexes, a large number of strong correlations emerged, the most notable ones being the strong positive coefficients between cigarettes sold in the early 1950s and lung cancer mortality in middle-aged males in the early 1970s, between gross internal product or meat consumption and cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 9 publications
3
33
0
Order By: Relevance
“…Interestingly, at variance with other countries of the northern hemisphere where north-south gradients in melanoma mortality rates are observed, in Italy, higher rates have been documented in the north than in the south. 32 It has been suggested that the relation between sun exposure and melanocytic nevi may be complex with a parabolic dose-response curve. 33 Ultraviolet light radiation may have both a direct action on melanocytes and an indirect one through the immune system.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, at variance with other countries of the northern hemisphere where north-south gradients in melanoma mortality rates are observed, in Italy, higher rates have been documented in the north than in the south. 32 It has been suggested that the relation between sun exposure and melanocytic nevi may be complex with a parabolic dose-response curve. 33 Ultraviolet light radiation may have both a direct action on melanocytes and an indirect one through the immune system.…”
Section: Resultsmentioning
confidence: 99%
“…Sigurdson et al, (1999) found that high fat consumption 1 year before diagnosis of TC was associated with an increased risk of TC. TC was also associated with consumption of dairy products (Decarli and La Vecchia, 1986, Davies et al, 1996, Ganmaa et al, 2002, Garner et al, 2003, Stang et al, 2006. Dairy products, particularly milk and cheese, contain the female sex hormones estrogen and progesterone (Ganmaa et al, 2002).…”
Section: Diet and Nutritionmentioning
confidence: 99%
“…Diet has been associated with testicular cancer in several studies. 43,80,85,[144][145][146][147][148] Despite the inconclusive nature of these findings, a recent article states: ''The timing of the testicular cancer trend is consistent with a dietary origin, and the search for candidates should extend beyond hormonal agents to include those capable of causing genetic damage.'' 116 .…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…High intake of fat has been associated with increased risk of testicular cancer, 145,147 a finding consistent with many reports for cancers at other hormonally influenced sites such as breast, prostate, colon and ovary. 147,[149][150][151] Dairy products, particularly milk and cheese, 85,144,146,148,152 have been linked to testicular cancer. These foods contain the female sex hormones estrogen and progesterone.…”
Section: Lifestyle Factorsmentioning
confidence: 99%
See 1 more Smart Citation